Developmental reading 1 - Bernardo, Alejandro S (Manila, 2009)
This book was designed as a response to the Commission on Higher Education's mandate of offering a course in college reading to assist the students in honing their comprehension skills deemed necessary for coping with the demands of various content areas
Keywords: Developmental reading